The Social Work Regulator and Professional Identity: A Narrative of Lord and Bondsman. (1st May 2020) - Simpson, Murray; Daly, Maura; Smith, Mark
Abstract: Since the early 2000s, in a development since mirrored throughout much of the Anglophone world, social work across UK jurisdictions has been subject to external regulation. Whilst a key justification for regulation was to enhance professional identity, there is little evidence that it has done so. Indeed, a growing literature points out conflictual and unproductive relationships between the social work profession and its regulators, within which a marked power imbalance in favour of the regulator is apparent. In this article, we illustrate the nature of this imbalance theoretically by drawing upon the classic philosophical narrative, developed by Georg Willhelm Friedrich Hegel (1770–1831), of the 'lord and bondsman'. We seek to demonstrate the utility of the Hegelian narrative using data from a study into the views of social workers on how they understand their professional identities, focusing specifically on those aspects of the study that address the place of regulation in this process. Whilst exposing some fundamental problems in the regulatory relationship, the lord and bondsman narrative may also offer some possibility of a way forward through identifying these dialectics as a step towards a more self-conscious professional maturity.